Reactive Probe for Fluorescent Detection of Norepinephrine Based On an Excited-State Intramolecular Proton Transfer (ESIPT) Mechanism - Haque, Rajibul; Ghosh, Souma; Banerjee, Rajkumar; Maity, Debabrata (Synlett, 2025)
Norepinephrine is a key neurotransmitter that plays a critical role in the sympathetic nervous system. Its misuse and lack of regulation is closely associated with the progression of different central nervous system syndromes and neurodegenerative disorders. Herein, a reactive probe based on an excited-state intramolecular proton transfer (ESIPT) mechanism is reported for the selective fluorescent detection of norepinephrine under physiological conditions and in live cells.
Keywords: fluorescent probes; norepinephrine; excited-state intramolecular proton transfer; 2-(2′-hydroxyphenyl)benzothiazole; Live-cell imaging